Submolecular Ligand Size and Spacing for Cell Adhesion. Issue 27 (31st May 2022) - Kim, Yuri; Koo, Thomas Myeongseok; Thangam, Ramar; Kim, Myeong Soo; Jang, Woo Young; Kang, Nayeon; Min, Sunhong; Kim, Seong Yeol; Yang, Letao; Hong, Hyunsik; Jung, Hee Joon; Koh, Eui Kwan; et al.
Abstract: Cell adhesion occurs when integrin recognizes and binds to Arg–Gly–Asp (RGD) ligands present in fibronectin. In this work, submolecular ligand size and spacing are tuned via template‐mediated in situ growth of nanoparticles for dynamic macrophage modulation. To tune liganded gold nanoparticle (GNP) size and spacing from 3 to 20 nm, in situ localized assemblies of GNP arrays on nanomagnetite templates are engineered. 3 nm‐spaced ligands stimulate the binding of integrin, which mediates macrophage‐adhesion‐assisted pro‐regenerative polarization as compared to 20 nm‐spaced ligands, which can be dynamically anchored to the substrate for stabilizing integrin binding and facilitating dynamic macrophage adhesion. Increasing the ligand size from 7 to 20 nm only slightly promotes macrophage adhesion, not observed with 13 nm‐sized ligands. Increasing the ligand spacing from 3 to 17 nm significantly hinders macrophage adhesion that induces inflammatory polarization. Submolecular tuning of ligand spacing can dominantly modulate host macrophages. Abstract : Submolecular tuning of ligand size and spacing is demonstrated via template‐mediated in situ growth of nanoparticles. It is revealed that submolecular ligand spacing stimulates integrin binding to facilitate the adhesion‐mediated pro‐regenerative polarization of macrophages. Increasing ligand spacing only significantly inhibits macrophage adhesion, whereas increasing both ligand size and spacing slightly hinders macrophage adhesion.